1998
DOI: 10.1103/physrevb.58.16130
|View full text |Cite
|
Sign up to set email alerts
|

Absorption-edge anisotropy inReS2andReSe2layered semiconductors

Abstract: Polarization-dependent absorption measurements of ReS 2 and ReSe 2 single crystals have been carried out in the temperature range between 25 and 500 K. A significant shift towards lower energies has been observed in the transmittance spectra of Eʈb polarization with respect to those corresponding to EЌb polarization. Analysis reveals that the absorption edges of ReS 2 and ReSe 2 are indirect allowed transitions. The parameters that describe the temperature dependence of the absorption edges with different pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 25 publications
(25 reference statements)
8
67
0
Order By: Relevance
“…Upon transition from 1T (1H) to the distorted 1T structure, the energy gain is 1.1 (0.9) eV per ReS 2 molecule. In the distorted 1T structure, the Re atoms in the layer dimerize in such a way that they form a zigzag Re-Re chain extending along one of the lattice vectors 16,17 . Interestingly, by geometry consideration, the presence of the Re chains eliminates the energy benefit for the ReS 2 layers to order in Bernal (AB) or rhombohedral (ABC) stacking that occurs in other sTMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Upon transition from 1T (1H) to the distorted 1T structure, the energy gain is 1.1 (0.9) eV per ReS 2 molecule. In the distorted 1T structure, the Re atoms in the layer dimerize in such a way that they form a zigzag Re-Re chain extending along one of the lattice vectors 16,17 . Interestingly, by geometry consideration, the presence of the Re chains eliminates the energy benefit for the ReS 2 layers to order in Bernal (AB) or rhombohedral (ABC) stacking that occurs in other sTMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Influenced by the covalent bonding, the lattice becomes a distorted 1T structure wherein Re atoms in the layer form a zig-zag Re-Re chain (Figure 4). [13,51,52] Because of the presence of Re chain inside each layer, energy difference of ReS2 layers when sliding from one layer to other becomes very nominal and therefore lacks order in stacking. In addition, one extra electron on the Re atoms results in significantly less intra-layer polarization and weakens the van der Walls interaction in interlayer.…”
Section: Interlayer Coupling and Polytypismmentioning
confidence: 99%
“…In contrast ReS2 has reduced crystal symmetry which gives rise to anisotropic inplane optical properties. [21,51,[70][71][72] Research related to the electron-electron and hole-hole interactions in the excited state concluded that the anisotropic optical absorption on ReS2 was due to strongly bound excitons. The triclinic crystal structure of ReS2 leads to polarization dependent optical absorption.…”
Section: Excitonic and Absorption Propertiesmentioning
confidence: 99%
“…This is well consistent with the previous reports. [11][12][13] For the thin samples, a distinct absorption peak at around 1.3 eV is found. Compared with the PTR measurements that will be discussed later, this absorption peak is believed to originate from the E ex 1 excitonic transition.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports of absorption experiments only observed the indirect band gap. [11][12][13] In this work, the indirect band-edge transition is found to shift toward higher energy with decreasing the sample thickness, and for very thin samples several direct band-edge excitonic transitions are observed for the first time in the absorption spectra. On the other hand, electrical conductivity is measured and Hall measurement is performed, both at different temperatures ranging from 20 to 300 K. The activation energy is then derived from the Arrhenius plots of the conductivity and the Hall concentration.…”
Section: Introductionmentioning
confidence: 99%